Geopolitics, aid and growth - Dreher, Axel; Eichenauer, Vera; Gehring, Kai (Discussion paper series, 2014)
We investigate the effects of short-term political motivations on the effectiveness of foreign aid. Specifically, we test whether the effect of aid on economic growth is reduced by the share of years a country has served on the United Nations Security Council (UNSC) in the period the aid has been committed, which provides quasi-random variation in aid. Our results show that the relationship of aid with growth is significantly lower when aid has been committed during a country’s tenure on the UNSC. We derive two conclusions from this. First, short-term political favoritism reduces growth. Second, political interest variables are inadequate as instruments for overall aid, raising doubts about a large number of results in the aid effectiveness literature.